Environmental effect on health: Air pollution and smoke - Marianne Frieri; Krishan Kumar; Anthony Boutin (Wolters Kluwer Medknow Publications, 2016)
This review has discussed various topics related to environmental health. The major findings highlighted are air pollution, children and adult vulnerability, cytokines related to interleukin-33, thymic stromal lymphopoietin, tobacco smoke related to neonates, women, and their families, and perinatal outcomes. The Emergency Department was also highlighted related to asthma and air pollution concentrations within the emergency department, admissions for respiratory effects in pediatrics, and in patients with asthma that often present to the emergency department for treatment for acute exacerbations.